Beyond Alkaloids: Novel Bioactive Natural Products From Lobelia Species - Zheng, Qinfang; Wang, Ye; Zhang, Shuihan (Frontiers in Pharmacology, 2021)
In this work, we reviewed the progress in the phytochemical and biological investigations of bioactive components derived from medicinally valuable Lobelia species. In the last 60 years, Lobelia has garnered significant attention from the phytochemist from around the world, majorly due to the discovery of the bioactive piperidine alkaloid, lobeline in the early 1950s. Later, lobeline underwent clinical trials for several indications including the treatment of ADHD and a multicenter phase 3 trial for smoking cessation. Subsequently, several other alkaloids were also derived from different Lobelia species and investigated for their pharmacological characteristics. In the last few years, however, the research focus has started shifting to the characterization of the other novel chemical classes. The major shift has been due to the structurally resembling alkaloid components, essentially sharing similar pharmacological, physicochemical, and toxicological profiles including severe cardiotoxicity. In this work, we reviewed this progress with special attention to understanding the molecular mechanisms of the novel bioactive components.